Detection of Small Amounts of Yests, Bacteria and Phages Particles as Biological Objects in Agarose Gel Samples Using Uncoated Plate Acoustic Wave Sensor. (2017) - Anisimkin, Vladimir I.; Kuznetsova, Iren E.; Kolesov, Vladimir V.; Sorokin, Vladimir V.; Skladnev, Dimitry A.; Caliendo, Cinzia; Verona, Enrico
Abstract: Capabilities of the acoustic wave sensing without using special sorbent films are studied at normal conditions with the use of three types of biological objects to detect coliphages, bacteria and yeasts in ordinary liquid rich growth Luria-Bertani media as well as for these biological objects immobilized in agarose hydrogel in various concentrations (and in highly diluted Luria-Bertani broth as reference media also). The method does not require special bath and large volume of test samples (∼100 μL), demonstrates high long-term stability, but possesses some inherent limitations to be discussed. Dilution of the analytes in the reference media is detected to change electric conductivity, but not viscosity of the suspension. The values of the conductivity σ are around 0.5 S/m. The minimum detectable bacteria concentration is estimated as 100 - 1000 cell/ml.